Theory of structure and mechanics of fibrous assemblies - Neckar, Bohuslav (Woodhead Pub. India, 2012)
This book discusses a system of theoretically derived inherent laws of fibrous assemblies. It includes original results of theoretical research carried out on fibrous assemblies. The topics of this book include fiber and pore characteristics in fibrous assemblies, fiber packing density and fiber orientation in fibrous assemblies, tensile behavior of fiber bundles and multiaxial systems, fiber-to-fiber contacts and compression behavior of fibrous assemblies. The chapters of this book are started with definitions, terminologies and fundamental relations. Then the theoretical models are presented from initial assumptions through mathematical derivations to final relations. Such theoretical results are mostly compared with experimental results.
Keywords: Textile fabrics -- Mechanical properties -- Mathematical models.; Textile fabrics -- Microstructure -- Mathematical models.; elektronické knihy; electronic books